War, Aggression and State Crime: A Criminological Analysis of the Invasion and Occupation of Iraq - Kramer, Ronald C. (The British journal of criminology, 2005)
In this article, we argue that the 2003 US/UK invasion and occupation of Iraq was a form of state crime and offer a criminological analysis of the event. First, we describe how the war on Iraq violated the UN Charter and international humanitarian law. Then, we provide a narrative analysis of the historical and contemporary origins of this crime through the lens of an integrated model for the study of organizational deviance that has proved useful in the analysis of a number of other upper-world crimes. A key part of our explanation of this war resides in the dynamics of America's long-standing will to empire coupled with the imperial designs of neoconservative policy makers within the Bush administration